2011
DOI: 10.1007/s00024-011-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Serpentinized Ultrabasic Rocks in NW Turkey

Abstract: Serpentinized ultrabasic rocks crop out at various places in the northwestern part of Turkey. They are the foundation rocks of some architecture and the ground under road bases in many areas. They are also frequently used for indoor work such as tables, shafts, pilasters, jambs for chimney pieces and ornaments of different kinds. Owing to their economic importance, in situ geophysical and geotechnical studies were conducted to determine their dynamic engineering parameters such as: P-and S-wave velocities, Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 27 publications
6
18
0
1
Order By: Relevance
“…Similar positive correlations have been observed also for other ultramafic rocks and several authors have recommended that there is a direct and strong correlation between these two mechanical parameters in rocks (Kurtulus et al, 2011), hence an indirect estimation of one from the other can be made. The moderate correlation shown for the Gerania peridotites indicates that such an estimation involves large errors.…”
Section: Discussionsupporting
confidence: 80%
“…Similar positive correlations have been observed also for other ultramafic rocks and several authors have recommended that there is a direct and strong correlation between these two mechanical parameters in rocks (Kurtulus et al, 2011), hence an indirect estimation of one from the other can be made. The moderate correlation shown for the Gerania peridotites indicates that such an estimation involves large errors.…”
Section: Discussionsupporting
confidence: 80%
“…The P and S seismic velocities of the layers were calculated using the Esos-Seisimager evaluation program. Using the experimental equations found in studies [32][33], [25] and [34], the elasticity modulus of rocks was determined using P and S seismic velocities values. The mean calculated P and S wave velocities were given in Table 1.…”
Section: Field Studiesmentioning
confidence: 99%
“…The same experiments were then repeated after samples were saturated with water and were given in Table 2. The test results of studies by [37], [12] and [25] showed that seismic velocity values parallel to foliation were always higher than those perpendiculars to foliation and this situation is due to the anisotropic properties of the rock. Based on this, the Pwave velocities (Vp) of cubic rock samples in this study were separately determined according to [38] standards , with a PUNDIT7-UPV E48 brand seismic velocity instruments and same results were obtained from the experiments.…”
Section: Ultrasonic Pulse Velocity Measurements (Upv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma and Singh (2010) proposed a linear equation with coefficient of determination at 0.93 so as to estimate the uniaxial compressive strength through the velocity of longitudinal waves (Sharma and Singh, 2010). Kurtulus et al (2011) offered a linear equation with coefficient of determination at 0.92 so as to estimate the uniaxial compressive strength in serpentine stone through the velocity of longitudinal waves (Kurtulus et al, 2011). Altindag (2012) proposed an exponential equation with coefficient of determination at 0.79 so as to estimate the uniaxial compressive strength in sedimentary rocks (Altindag, 2012).…”
Section: Introductionmentioning
confidence: 99%